Evolution of Water Quality Regulations in the United States and Florida - Kati W. Migliaccio; Yuncong Li; Thomas A. Obreza (EDIS)
Revised! Water is essential to sustain life. Not only do we all need a certain quantity of water each day, but the quality of the available water is also critical. Water quality protection in the United States evolved from initially ensuring navigability of waterways to protecting our natural ecosystems. This 5-page fact sheet provides a background for understanding water quality and how it is evaluated and regulated in the U.S. with particular focus on the state of Florida. Written by Kati W. Migliaccio, Yuncong Li, and Thomas A. Obreza. Published by the UF Department of Agricultural and Biological Engineering, January 2011.